Depletion or expansion? Understanding the effects of support policy use on employee work and family outcomes. (25th September 2017) - Li, Andrew; Butler, Adam; Bagger, Jessica
Abstract: Past research on the effects of employees' use of work–family support policies tends to draw on a depletion perspective suggesting that using these policies may reduce work–family conflict. The emphasis on depletion fails to consider the expansion perspective that assumes that using work resources may enrich family functioning. Using a sample of 113 matched employee–supervisor pairs and a 1‐month separation between predictor and criterion measurement, we found support for the expansion rather than the depletion perspective. Specifically, the relationships between support policy use and employee job satisfaction and family efficacy (but not organisational citizenship behaviour) were mediated by work‐to‐family enrichment; these effects were realised only for employees with high levels of family identity. In contrast, no support was found for family‐to‐work conflict as a mediator of the model.